2011
DOI: 10.1021/la203384f
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pickering Emulsion Gels Formed by Droplet Bridging

Abstract: We experimentally characterize the microstructure and rheology of a carefully designed mixture of immiscible fluids and near-neutral-wetting colloidal particles. Particle bridging across two fluid interfaces provides a route to highly stable gel-like emulsions at volume fractions of the dispersed phase well below the random close-packing limit for spheres. We investigate the microstructural origins of this behavior by confocal microscopy and reveal a percolating network of colloidal particles that serves as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 51 publications
6
106
0
Order By: Relevance
“…They proposed that bridging occurs where there are strong repulsive interactions between the particles and they form dilute monolayers at the oil-water interface [40]. Bridging occurs when particles on opposing interfaces interlock as the interfaces come together [41,42]. French et al [43] demonstrated that for particle bridging to occur, there must be insufficient particles present to stabilise the interfacial area in the emulsion and the particles must be preferentially wet by the continuous phase.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
“…They proposed that bridging occurs where there are strong repulsive interactions between the particles and they form dilute monolayers at the oil-water interface [40]. Bridging occurs when particles on opposing interfaces interlock as the interfaces come together [41,42]. French et al [43] demonstrated that for particle bridging to occur, there must be insufficient particles present to stabilise the interfacial area in the emulsion and the particles must be preferentially wet by the continuous phase.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
“…The most familiar example is of sand which, when wetted with small amounts of water, develops sufficient yield stress to allow construction of elaborate sand castles [1][2][3][4]. The same is true for particles-in-liquid suspensions: Addition of a small amount of a second immiscible liquid can create a network which endows the suspension with a yield stress [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, open pore morphologies can be realized readily in such systems [9,[16][17][18] with immediate relevance to applications in which chemical transport or fluid retention must be combined with mechanical strength. Indeed applications to materials science are not restricted to suspensions with capillary forces-a diverse set of particle/fluid/liquid mixtures can, depending on the materials and composition, yield a variety morphologies of potential interest to materials science [15], including Pickering emulsions [8,19], particle-stabilized foams [20][21][22], bijels [18,23], wet granular materials [1,24,25], and liquid marbles [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Lee and coworkers recently reported on a similar bridging morphology in non-IL Pickering emulsions stabilized by hydrophobized silica microspheres [38]. In that study, the authors showed that only particles with a sufficiently large three-phase contact angle could bridge emulsion droplets resulting in extensive percolating structures [38].…”
Section: Possible Mechanismsmentioning
confidence: 81%
“…In that study, the authors showed that only particles with a sufficiently large three-phase contact angle could bridge emulsion droplets resulting in extensive percolating structures [38]. Droplets in that system, however, were fully covered whereas the key feature of the IL-based system was exclusive bridging in the absence of droplet coverage.…”
Section: Possible Mechanismsmentioning
confidence: 99%